Neopterin Counters Vascular Inflammation and Atherosclerosis - Remina Shirai; Kengo Sato; Tomoyuki Yamashita; Maho Yamaguchi; Taisuke Okano; Kaho Watanabe‐Kominato; Rena Watanabe; Taka‐aki Matsuyama; Hatsue Ishibashi‐Ueda; Shinji Koba; Youichi Kobayashi; Tsutomu Hirano; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2018)
BackgroundNeopterin, a metabolite of GTP, is produced by activated macrophages and is abundantly expressed within atherosclerotic lesions in human aorta and carotid and coronary arteries. We aimed to clarify the influence of neopterin on both vascular inflammation and atherosclerosis, as neither effect had been fully assessed. Methods and ResultsWe investigated neopterin expression in coronary artery lesions and plasma from patients with coronary artery disease. We assessed the atheroprotective effects of neopterin in vitro using human aortic endothelial cells, human monocyte‐derived macrophages, and human aortic smooth muscle cells. In vivo experiments included a study of aortic lesions in apolipoprotein E–deficient mice. Neopterin expression in coronary artery lesions and plasma was markedly increased in patients with versus without coronary artery disease. In human aortic endothelial cells, neopterin reduced proliferation and TNF‐α (tumor necrosis factor α)–induced upregulation of MCP‐1 (monocyte chemotactic protein 1), ICAM‐1 (intercellular adhesion molecule 1), and VCAM‐1 (vascular cell adhesion molecule 1). Neopterin attenuated TNF‐α–induced monocyte adhesion to human aortic endothelial cells and the inflammatory macrophage phenotype via NF‐κB (nuclear factor‐κB) downregulation. Neopterin suppressed oxidized low‐density lipoprotein–induced foam cell formation associated with CD36 downregulation and upregulation of ATP‐binding cassette transporters A1 and G1 in human monocyte‐derived macrophages. In human aortic smooth muscle cells, neopterin suppressed angiotensin II–induced migration and proliferation via c‐Src/Raf‐1/ERK1/2 downregulation without inducing apoptosis. Exogenous neopterin administration and endogenous neopterin attenuation with its neutralizing antibody for 4 weeks retarded and promoted, respectively, the development of aortic atherosclerotic lesions in apolipoprotein E–deficient mice. ConclusionsOur results indicate that neopterin prevents both vascular inflammation and atherosclerosis and may be induced to counteract the progression of atherosclerotic lesions. Consequently, neopterin could be of use as a novel therapeutic target for atherosclerotic cardiovascular diseases.